Dinamika Pemahaman Tuhan dalam Pendidikan Islam: Sintesis Filsafat dan Kajian Antropologis - Mahfud (Kartika: Jurnal Studi Keislaman, 2025)
This study examines the dynamics of understanding the concept of divinity in Islamic education through a synthesis of philosophical and anthropological approaches. Employing library research and a descriptive qualitative framework, it draws on classical Islamic philosophical texts (Al-Farabi, Ibn Sīnā, al-Ghazālī), theories of divine argumentation (ontological, cosmological), and key works in the anthropology of religion (Tylor, Durkheim, Eliade) that trace the evolution of belief and practice in socio-cultural contexts. A thematic analysis highlights the rational frameworks and socio-cultural contestations that shape the understanding of tawḥīd within Islamic curricula and pedagogical practices. Findings reveal that the philosophical approach provides a logical foundation for conceiving God as the Necessary Being and First Cause, while the anthropological perspective maps the transformation of the concept of divinity—from animism and totemism to hierophanic manifestations—along cultural trajectories. Integrating these approaches enriches Islamic curricula by embedding awareness of tawḥīd as both a source of knowledge and spirituality, in alignment with national education mandates to cultivate faithful and God-conscious individuals. These results affirm that Islamic education functions not merely as knowledge transfer but as a process of instilling vertical consciousness toward Allah SWT.